Supporting GUI exploration through USS tool - Silva, J. L.; Ornelas, J. D.; Silva, J. C. (Journal of Information Systems Engineering and Management, 2016)
Advances in usability and design techniques (e.g. user-centered design) try to facilitate the use of interactive systems. However, users still have to adapt to interactive systems, i.e. they have to learn the steps required to accomplish a task either by trial and error or by obtaining help. While advanced users are usually able to adapt without much effort this is far from being the case with beginners. Some interactive systems offer different interaction styles in an attempt to meet the needs of all types of user but this is not the case with all interactive systems. In this sense, we present an approach to support the use of any interactive system making use of enriched models and picture-driven computing to achieve tasks automation. The USS tool (User Support System) is the basis to the adaptation of interactive systems accordingly to the users' needs. The approach provides the foundation for the addition of help (based on demonstration) to any graphical user interfaces (GUI) facilitating learning and use. The work is illustrated by a case study and completed with a preliminary user evaluation which provides insights about the validity of the approach.